The Puritan origins of American patriotism - McKenna, George (Yale University Press, 2007)
In this absorbing book, George McKenna ranges across the entire panorama of American history to track the development of American patriotism. That patriotism, shaped by Reformation Protestantism and imbued with the American Puritan belief in a providential 'errand', has evolved over 350 years and influenced American political culture in both positive and negative ways, McKenna shows. The germ of the patriotism, an activist theology that stressed collective rather than individual salvation, began in the late 1630s in New England and travelled across the continent, eventually becoming a national phenomenon. Today, American patriotism still reflects its origins in the seventeenth century. By encouraging cohesion in a nation of diverse peoples and inspiring social reform, American patriotism has sometimes been a force for good. But the book also uncovers a darker side of the nation's patriotism: a prejudice against the South in the nineteenth century, for example; or a tendency toward nativism and anti-Catholicism. Ironically, a great reversal has occurred, and today the most fervent believers in the Puritan narrative are the former 'outsiders' - Catholics and Southerners. McKenna offers an interesting new perspective on patriotism's role throughout American history, and he concludes with trenchant thoughts on its role in the post-9/11 era.